Legal Loophole On Witness Protection In The 2019 Presidential Election Dispute In Constitutional Court Of The Republic Of Indonesia - Rudy Iskandar Ichlas, I Gusti Ayu Ketut Rachmi Handayani, Widayati (International Journal of Advanced Science and Technology, 2020)
The attitude of a party disadvantaged by witness testimony has the potential to threaten safety of the witness in Constitutional Court of the Republic of Indonesia, hereinafter referred to as MKRI. The problem of this study is how is the witness protection in the General Election Results Dispute, hereinafter referred to as PHPU, of the 2019 Presidential Election in the MKRI provided? The method used in this study is normative legal research (doctrinal research) which is presented in an analytical descriptive manner. The results of this study show that the witnesses protection in the PHPU of the 2019 Presidential Election in the MKRI is difficult to involve Witness and Victim Protection Agency, hereinafter referred to as LPSK. There is no legal basis that states that constitutional judges have the right to govern or request LPSK to provide witness protection in the PHPU of the 2019 Presidential Election. Legal loopholes that obstruct LPSK to contribute to the witness protection in the PHPU of the 2019 Presidential Election is due to Law of the Republic of Indonesia Number 31 of 2014 regarding Amendment to Law of the Republic of Indonesia Number 13 of 2006 concerning Witness and Victim Protection as a legal basis for LPSK is only intended for criminal disputes, not PHPU disputes. MKRI is passive in relation to witness protection involving LPSK because only MKRI witnesses who report criminally can be protected by LPSK based on Law of the Republic of Indonesia Number 31 of 2014 regarding Amendment to Law of the Republic of Indonesia Number 13 of 2006 concerning Witness and Victim Protection.